Assessment of residential satisfaction in high-rise condominium and terrace housing: case studies from Kuala Lumpur - Mohit, Mohammad Abdul; Abdul Rahim , Zaiton (Research Management Centre, IIUM, 2012)
Kuala Lumpur, the capital city of Malaysia, has been experiencing a rapid rate of urbanization over the last four decades. This has created the need for housing which initially started in a low density fashion in the city, but it gradually turn into high density because of increasing land price and shortage of land in the core urban areas. The growth of condos in Kuala Lumpur City during last the two decades, as high density housing, is a response to the growing demand for housing in the city. So far housing research in Malaysia is focussed on public or private low-cost with little attention paid to the growing condo sector. Therefore, a research need arises due to limited studies on the subject and further that due to more than one reason, Malaysian middle class city dwellers currently prefer to live in condos than their preferred terrace housing. Against the above backdrop, this paper provides a comparative assessment of residents’ satisfaction with condominiums of different ages – older (>10 years) and younger (<10 years) within Kuala Lumpur City. Three basic components of satisfaction – dwelling unit variables, dwelling unit support and neighbourhood facilities and management, have been studied. Two hundred respondents - 100 residing in older condos and another 100 living in younger condos participated in the survey. Findings from the study indicate that the residents of the older condos are not satisfied with the dwelling unit support services and management and over 40% of the residents are also planning to relocate due to current housing situation. On the contrary, the younger condo residents show a relatively high level of satisfaction with the dwelling unit support services and they are moderately satisfied with condo management. The older condos showed a more significant and positive relationship between the overall housing satisfaction and the tested variables as compared to the younger condos due to the age differences between the two types. Finally, the paper comes up with three basic issues where immediate attentions are required to improve condo management and enhance residents’ satisfaction. Since 1970s, Malaysia is experiencing rapid economic growth which led to rapid urbanization as well. This rapid urbanization is associated with growing urban population and increasing household income. Thus, Malaysian government has facilitated various types of housing in order to accommodate different income groups. Despite design limitations such as lack of ventilation and natural lighting, double-storey terrace housing is considered as popular housing type among the middle income people in urban areas. However, empirical studies identified increase in crime rate in landed housing such as double-storey terrace house. In addition, design of double-storey terrace house also impacted on residents’ satisfaction. As a result, double-storey terrace house is found as the most modified houses in Malaysia. Thus, this research aims to appraise residential satisfaction in two double-storey terrace housing neighborhoods- Taman Sri Rampai (TSR) and Taman Keramat Permai (TKP) in Greater Kuala Lumpur. The research objectives and the questions were formulated based on a dynamic interaction approach which includes three main processes- cognitive, affective and behavioral. In order to examine and compare the residential satisfaction in two neighborhoods, five housing environment components of double-storey terrace housing such as physical features, housing support services, public facilities, social environment and neighborhood facilities were analyzed through residents’ levels of satisfaction. The research explored and compared the residents’ behaviors as a result of the residential satisfaction/ dissatisfaction. The main research data was obtained from a random sample of 220 survey questionnaires distributed equally among the residents of two neighborhoods. The data was analyzed by using SPSS. Reliability test was carried to examine the reliability of the questionnaire’s items. Descriptive and inferential statistics were used to examine the levels of satisfaction and to explore residents’ behaviors. The findings of the research indicate that the levels of residential satisfaction are generally low with physical features, housing support services, and social environment in two neighborhoods. On the other hand, residents’ satisfaction level was high with public facilities. While the levels of satisfaction are high with neighborhood facilities in TKP, they are moderate in TSR. The findings also explore that the most modified spaces in double-storey terrace house are essential spaces followed by complemental spaces and special spaces. Finally, the findings show that two-thirds of the residents in TKP intend to stay in their current area while half of residents in TSR prefer to stay. Recommendations are directed to increase the low levels of satisfaction among residents in two neighborhoods. Future studies are suggested to extend the study on different locations of double-storey terrace housing, different demographic characteristics of residents, and different socio-economic characteristics of residents as well.